2018
DOI: 10.3390/rs10071076
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for the Estimation of Aquaculture Production Based on Earth Observation Data

Abstract: Aquaculture makes a crucial contribution to global food security and protein intake and is a basis for many livelihoods. Every second fish consumed today is produced in aquaculture systems, mainly in land-based water ponds situated along the coastal areas. Satellite remote sensing enables high-resolution mapping of pond aquaculture, facilitating inventory analyses to support sustainable development of the planet's valuable coastal ecosystems. Free, full and open data from the Copernicus earth observation missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 63 publications
0
35
0
4
Order By: Relevance
“…Clauss et al [54] conducted a study to estimate rice production and rice area in Vietnam. Ottinger et al [55] observed aquaculture ponds using more than 500 Sentinel-1 scenes and an object-based analysis method and revealed that Sentinel-1 SAR with high spatial resolution can be used for monitoring aquaculture ponds in Vietnam and China. The author showed this approach has great potential for global production projections.…”
Section: Introductionmentioning
confidence: 99%
“…Clauss et al [54] conducted a study to estimate rice production and rice area in Vietnam. Ottinger et al [55] observed aquaculture ponds using more than 500 Sentinel-1 scenes and an object-based analysis method and revealed that Sentinel-1 SAR with high spatial resolution can be used for monitoring aquaculture ponds in Vietnam and China. The author showed this approach has great potential for global production projections.…”
Section: Introductionmentioning
confidence: 99%
“…Using some of the world's most significant aquaculture production regions as case studies, i.e., the Mekong, Red, Pearl and Yellow Rivers, the method achieved an overall classification accuracy of 0.83. Extending this dataset, Ottinger et al [172] integrated the remotely-sensed pond maps with pond yield statistics from the literature to estimate aquaculture production in each mega delta, highlighting the great potential of EO for monitoring and management of aquaculture in these regions.…”
Section: The Earth Observation Potential For the Analysis Of Flood Anmentioning
confidence: 99%
“…This first continental-scale, multi-decadal assessment of annual mangrove distribution showed that mangrove forest extent in Australia peaked in 2010 and has since declined by about 240 km 2 [139]. Several recent studies have used Sentinel-1 SAR time series data to map the distribution of rice paddies and aquaculture ponds in river deltas, taking advantage of the unique seasonal inundation dynamics and microwave backscattering characteristics of these features [171,172,[188][189][190]. Advances in SAR-based mapping of aquaculture ponds are already covered in the previous chapter, and therefore, are not repeated here.…”
Section: Earth Observation Potential For Land Cover and Land Use Infomentioning
confidence: 99%
“…Several studies pointed out that aquaculture has the potential to reduce poverty across the world [2][3][4]. Due to population growth, aquaculture as a controlled system of protein production is powerful in contributing to food security and covering future nutrition demands, which positively influences human well-being [5,6].…”
Section: Introductionmentioning
confidence: 99%